2019
DOI: 10.18510/hssr.2019.7227
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Google Classroom as an Instructional Media: A Case of State Islamic Institute of Kendari, Indonesia

Abstract: Purpose: This study aims to explore the effectiveness of Google Classroom in the learning process at the State Islamic Institute of Kendari. Methodology: The research method used in this study is a qualitative method, in-depth interview. Data collection was done through interview sessions with students from the Faculty of Teacher Training and Education. Main Findings: The findings showed that the use of Google Classroom was effective with various limitations: (1) not all students got an account wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 17 publications
10
87
0
17
Order By: Relevance
“…In Google Classroom, teachers can provide materials on the subject being taught. The teachers can post some teaching materials, assign tasks to students, and upload the students' grades so that they can see the scores obtained in the course instantly [49]. Teachers chose Google Classroom because most schools have provided Google Apps for Education, an online learning facility for teachers and students to open a space for online discussions.…”
Section: Technology Used In Indonesian Online Learningmentioning
confidence: 99%
“…In Google Classroom, teachers can provide materials on the subject being taught. The teachers can post some teaching materials, assign tasks to students, and upload the students' grades so that they can see the scores obtained in the course instantly [49]. Teachers chose Google Classroom because most schools have provided Google Apps for Education, an online learning facility for teachers and students to open a space for online discussions.…”
Section: Technology Used In Indonesian Online Learningmentioning
confidence: 99%
“…Secondly, the Wi-Fi in the campus was weak and students didn't have proper internet to attend online discussions or to submit their assignment. This throw lights on what could go wrong with such systems and shows the future initiatives that should be taken related to accessibility, connectivity and affordability among the users [19].Furthermore, a Google Classroom study shows it encouraged writing and editing since students did not have to recopy their work [20].…”
Section: E-learning Platformsmentioning
confidence: 99%
“…In the excerpts below, the participants shared their experiences about what web-based platforms they used in learning English: Almost all the participants applied Google Classroom and WhatsApp in learning English and they also used other learning platforms independently such as google translate, Cake and U-Dictionary to dive into word meanings, in which some words may be difficult to comprehend. The use of WhatsApp and Google Classroom as supporting applications in e-learning is defined to be more efficient as the teacher guide the students to improve their learning ability and skills (Alim et al, 2019;Gon & Rawekar, 2017). Furthermore, Sujarwo et al (2020) in his study found out that mostly students used Google Classroom and WhatsApp in e-learning during this pandemic.…”
Section: Technology Adaptationmentioning
confidence: 99%